2010
DOI: 10.1007/s10735-010-9260-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in extra cellular matrix remodelling and re-expression of fibronectin and tenascin-C splicing variants in human myocardial tissue of the right atrial auricle: implications for a targeted therapy of cardiovascular diseases using human SIP format antibodies

Abstract: Cardiovascular diseases are accompanied by changes in the extracellular matrix (ECM) including the re-expression of fibronectin and tenascin-C splicing variants. Using human recombinant small immunoprotein (SIP) format antibodies, a molecular targeting of these proteins is of therapeutic interest. Tissue samples of the right atrial auricle from patients with coronary artery disease and valvular heart disease were analysed by PCR based ECM gene expression profiling. Moreover, the re-expression of fibronectin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 56 publications
3
28
0
Order By: Relevance
“…Studies have demonstrated the participation of fibrillar collagen, fibronectin, and phenotypically transformed fibroblasts (myofibroblasts) on myocardial scarring. Changes in number and distribution of these structures affect myocardial complacence, with consequent alteration of systolic and diastolic function (heRPeL et al, 2006;FRANz et al, 2010). Phenotypically transformed fibroblasts (myofibroblasts) are cells responsible for the production of fibronectin and collagen.…”
Section: Clinic and Surgerymentioning
confidence: 99%
“…Studies have demonstrated the participation of fibrillar collagen, fibronectin, and phenotypically transformed fibroblasts (myofibroblasts) on myocardial scarring. Changes in number and distribution of these structures affect myocardial complacence, with consequent alteration of systolic and diastolic function (heRPeL et al, 2006;FRANz et al, 2010). Phenotypically transformed fibroblasts (myofibroblasts) are cells responsible for the production of fibronectin and collagen.…”
Section: Clinic and Surgerymentioning
confidence: 99%
“…22 In cardiac tissue of patients suffering from coronary artery disease who underwent cardiac surgery for revascularization, a distinct re-occurrence of fetal variants of tenascin-C could be evidenced on the mRNA as well as on the protein level. 8 By comparative analysis of tissue samples taken from different regions within the human heart, in particular the right atrial auricle, which is localized near the right atrium and the left side of the interventricular septum, it could be demonstrated that this reexpression phenomenon occurs in the whole organ. This observation speaks well for the fact that cardiac tissue remodeling is an all-encompassing ischemia induced effect, which is not exclusively restricted to the ischemic area.…”
Section: Tenascin-c In Ischemic Cardiomyopathy and Valvular Heart Dismentioning
confidence: 99%
“…23 Among the different fetal splicing variants of Tenascin-C, especially the A1 domain containing molecule seems to be overexpressed in remodelled human cardiac tissue from patients with coronary artery disease. 8,23 Detailed analysis of the protein deposition patterns of A1 domain containing tenascin-C in human cardiac tissue revealed a spatial association to areas of cardiac interstitial fibrosis as well as vessel structures. The vascular deposition is clearly perivascular on the extra-luminal side of the endothelial basement membrane.…”
Section: Tenascin-c In Ischemic Cardiomyopathy and Valvular Heart Dismentioning
confidence: 99%
See 2 more Smart Citations